2020
DOI: 10.1021/acs.jpca.9b09148
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Tetra-N-phenylbenzidine: Biphenyl as the Origin of Room Temperature Phosphorescence

Abstract: Amorphous purely organic thin films are able to show efficient phosphorescence under ambient conditions at room temperature. This opens the perspective to a wide range of new applications, which have attracted lots of interest in the field of material science recently. Therefore, an increasing number of different molecules displaying room temperature phosphorescence (RTP) have already been reported. Whereas the efficiency, the lifetime, or the oxygen sensitivity is frequently discussed, the origin of RTP mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Further, we recently reported that the origin of phosphorescence for TPB is the biphenyl motif. [ 51 ] Based on this, our group pursued several approaches with different side groups and substituents to extend the phosphorescence lifetime even more, where the presented one turned out to be most efficient.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Further, we recently reported that the origin of phosphorescence for TPB is the biphenyl motif. [ 51 ] Based on this, our group pursued several approaches with different side groups and substituents to extend the phosphorescence lifetime even more, where the presented one turned out to be most efficient.…”
Section: Figurementioning
confidence: 99%
“…The investigation of the emission properties shows the biluminescent behavior of our targets, i.e., the simultaneous emission of fluorescence and phosphorescence. Since PMMA itself emits by excitation at 275 nm [ 51 ] (Figure 2a and Figure S12, Supporting Information), data evaluation for PMMA samples will only be performed with an excitation wavelength λ exc = 300 nm. The position of the fluorescence and phosphorescence peaks of the four targets are nearly unaffected by excitation wavelength and matrix ( Table 1 ).…”
Section: Figurementioning
confidence: 99%
“…For example, 22Cz may be considered as a bis(biphenyl) derivative, a ring‐fused 2,2’‐dialkoxybiphenyl, or simply a twisted p ‐quaterphenyl. The power of such an approach was well evidenced in a recent report by Fries et al, which revealed that the origins of room temperature phosphorescence (RTP) in tetra‐ N ‐phenylbenzidine were a consequence of its biphenyl core [30] …”
Section: Introductionmentioning
confidence: 97%
“…BPAB displays blue single-molecule RTP peak at 475 nm with two shoulders, as reported previously. 27,31 While HLB-NTAB and HLB-NIAB exhibit green and yellow RTP at 509 nm and 586 nm (Fig. S9b and S9c), corresponding to their single-molecule phosphorescence, respectively.…”
Section: Resultsmentioning
confidence: 99%